BEBERAPA FAKTOR YANG TERKAIT DENGAN KEBIASAAN MEROKOK PADA SISWA PRIA KELAS I DAN II SMK MUHAMMADIYAH 2 SEMARANG 2OO3 - Zuliyyati -; Margo Utomo; Sayono - (JURNAL LITBANG, 2004)
Smoking is a habit that is detrimental to human health. In one piece of cigarette there are more than four thousand toxic chemical such as nicotine,CO, Arsenic, and tar. The prevalence of smokers in Indonesia has reached 70% of population, and 20% of them between I 5 ' 18 years of age (school age).This research is intended to find out the factors related with smoking on the students of SMI( Muhammadiyah 2 Semarang. The result of the research shows the 90%t of students are smokers. The factor of age, has significant correlation wilh the smoking habit while thefactors offamily, peer, teacher, and idolfigures do not hatte s igrificant correlation.Key words: smoking, students, age.